A charge and size-switchable Au2Pt nanosystem for deep-tumor penetration and combinatorial therapy of ocular uveal melanoma - Lingdan Kong; Linxin Chen; Pingping Huang; Linghong Wang; Kang Han; Xiaoqian Shi; Yue Zhang; Jizhen Wang; Yunhai Tu; Yuqin Wang; Yong Liu (Chemical Engineering Journal, 2026)

ERS-mediated metabolic toxicity: The IRE1α/XBP1s pathway as a critical driver of Cr(VI)-Induced disruption in glucose and lipid metabolism - Limin Zhang; Meina Wu; Luxi Tu; Lanhao Liu; Chunyue Wu; Wanwei Li; Yumei Liu; Mengxiao Luan; Xiaolin Han; Fengjiao Tan; Qin Wang; Xiaohong Li (Chemico-Biological Interactions, 2026)

Global cropland expansion amplifies the risk of compound dry and hot events under climate change - Haiyang Tu; Guoyong Leng; Linfei Yu; Lei Yao; Jiali Qiu; Lubin Han (Journal of Hydrology, 2026)

Bioinspired artificial lipase with engineered hydrophilic microenvironment for oriented substrate binding and structured lipids preparation - Han Liu; Keyu Xing; Shaoyi Yu; Jia Tu; Yanna Jiao; Liguang Xu; Wei Chen; Pei Jia; Zhou Xu (Food Research International, 2026)

Inactivation of Staphylococcus aureus on eggshells by combined slightly acidic electrolyzed water and UV: Influence factors, mechanistic insights, and penetration risk evaluation - Yitian Zang; Yao Zang; Yingjie Feng; Mingming Tu; Haojie Zhu; Jiahong Han; Shan Bing; Yanjiao Li; Xianghui Zhao; Nengshui Ding; Guoyun Wu (Food Control, 2026)

Interactions between medicinal plants and rhizospheric microbial secondary metabolites: Mechanisms, effects, and biotechnological applications - Karlia Meitha; Chen-Hui Kuo; Tu-Trinh Thi Truong; Chieh Chang; Tsai-Wen Hsu; Miaw-Ling Chen; Chao-Li Huang; Takashi Gojobori; Cheng-Han Yang (Ecological Genetics and Genomics, 2026)

Stress-homogenization tailoring via 2D-seed-mediated template growth for high-efficiency perovskite solar cells - Chenyun Wang; Chuanzhen Shang; Bin Zhou; Duo Qu; Shasha Wang; Wei Jia; Linwei Li; Qiang Guo; Ruilin Han; Wenying Zhao; Fan Xu; Jihuai Wu; et al. (Chemical Engineering Journal, 2026)

Discovery of Novel Antimicrobial Peptides from Casein via Integrated In Silico and Experimental Approaches: Identification and Mechanistic Insights - Miao Zhang; Zhicheng Wang; Liangbin Li; Haiyang Liu; Jiarun Han; Zhen Wu; Daodong Pan; Tao Zhang; Hui Liu; Maolin Tu (International Journal of Peptide Research and Therapeutics, 2026)

Menaquinone-4 protects CD8+ T cells from ferroptosis to enhance anti-tumor immunity - Jiarong Wang; Wen Wang; Simiao Fan; Liyun Liang; Huaibin Hu; Zenqing Song; Yu Zhang; Jiamei Zhang; Wanying Xiao; Biyu Zhang; Yaxin Li; Liang Luo; et al. (Science China Life Sciences, 2026)

AGR2-high cells drive a FOXM1-mediated pro-malignancy program in non-functional pancreatic neuroendocrine tumors (NF-PanNETs) and informatively predict patient outcomes - Junya Peng; Rui Jiang; Jiajuan Tu; Wanli Liu; Lu Ping; Ruikang Dun; Wenyu Zhang; Hao Chen; Yihong Shi; Xu Pan; Panpan Jia; Mengjie Li; et al. (Science Bulletin, 2026)

Bioremediation of cadmium-contaminated soil: Assessing the potential efficacy of Tetrahymena thermophila - Huijia Tang; Jing Zhang; Kaikang Hu; Jiawei Tu; Xue Hu; Lijun Luo; Jun Men; Yongyong Guo; Jian Han; Bingsheng Zhou (Journal of Environmental Sciences, 2026)

Mechanisms of action of natural plant-derived bioactive compounds in treating intestinal tight junctions dysfunction - Jiduo Han; Ziliang Xiao; Lingyu Yang; Jianfang Feng; Yi Jin; Meng Cheng; Liangxing Tu (Phytochemistry Reviews, 2026)

Numerical Ecohydraulic Modeling of Fish Habitat Conditions in Braided Rivers: The Role of Multi-Threaded Structures - Ruida Wang; Lijian Ouyang; Shicheng Li; Ayong Jiao; Chenyang Cao; Hao Zheng; Xiaowei Han; Shengzhi Zhou; Gang Xu; Xinggang Tu; Weiwei Yao (International Journal of Environmental Research, 2026)

Single-BDS GNSS-R water surface altimetry and performance analysis - Peiyuan Wang; Junqiang Han; Fang Cheng; Pengfei Zhang; Xiaolei Wang; Rui Tu; Weisheng Wang; Majid Gulayozov; Yaoming Li; Xiaochun Lu (Earth Science Informatics, 2026)

Hydration mechanism, mechanical properties and environmental performance of electrolytic manganese residue based total solid waste supersulfate cement - Dejun He; Junying Li; Guiji Tu; Mengjun Chen; Yunhui Han (Process Safety and Environmental Protection, 2026)

A PCR-enhanced UCNPs-WS2 fluorescence biosensor via dual quenching-dual recovery mechanism for rapid detection of Salmonella typhimurium - Lu Han; Min Chen; Qian Huang; Weijie Lan; Chong Wang; Leiqing Pan; Kang Tu (Food Research International, 2026)

Corrigendum to “Effects of germplasm type and geographic origin on juice quality of sea buckthorn: A comparative study of physicochemical properties, functional activities, and flavor chemistry” [Food Chem. 511 (2026) 148850] - Jingyi Ren; Ting Liu; Saige Zhang; Xingnan Wang; Wenzhi Lei; Yike Han; Guohao Tang; Mengtong Wang; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Chemistry, 2026)

A label-free magnetic bead affinity approach for direct target identification of herbal extract: Ganoderma lucidum as a case - Han Li; Bo Peng; Bo Li; Ting Li; Zihan Zhu; Pengfei Tu; Jun Li; Yuelin Song (Analytica Chimica Acta, 2026)

Human health risk assessment from potentially toxic elements (PTEs) in wild aesthetic plants (Cosmos): PTE concentration and distribution - Md Muzammel Hossain; Shuxin Tu; Song Han; Daochen Zhu; Abdullah Al Nahian (Environmental Monitoring and Assessment, 2026)

Differentiated biogeochemical pathways of antimony and arsenic immobilization: A comparative study on soil amendments under different remediation strategies - Yuezhong Chen; Han Tu; Pan Wu; Xuexian Li; Ling Li (Journal of Environmental Chemical Engineering, 2026)

Sunlight-driven sulfite/Cr(VI) photodegradation of potassium butyl xanthate in mining wastewater: pH-dependent radical evolution and the overlooked role of Cr(V) - Haidong Li; Yuankun Yang; Han Song; Yi Yang; Hui Gong; Xinwen Chen; Weiguo Tu; Xuemei Luo; Yu Liu; Shu Chen (Environmental Research, 2026)

Oxygen-driven restructuring of Fe5C2 inhibits the Iron-based catalyst CC coupling in CO2 hydrogenation - Baojian Chen; Lingyu Jia; Fugui He; Bingbing Liao; Shanshan Dang; Weifeng Tu; Yurong He; Noritatsu Tsubaki; Zhenzhou Zhang; Yi-Fan Han (Chemical Engineering Journal, 2026)

Drying-wetting cycles alter the balance between physical fragmentation and leaching during leaf litter decomposition: a laboratory incubation experiment - Le-Lin Yu; Rui-Jing Chai; Qi-Han Tu; An He; Le-Cheng Ai; Rong Mao (Plant and Soil, 2026)

Combining sun-induced chlorophyll fluorescence and seasonal climate forecast for 8-day dynamic in-season crop yield prediction - Chenxi Lu; Guoyong Leng; Lubin Han; Linfei Yu; Jiali Qiu; Lei Yao; Haiyang Tu; Xiaoyong Liao; Shengzhi Huang; Jian Peng (Agricultural and Forest Meteorology, 2026)

Weakening sensitivity of China’s terrestrial evapotranspiration to vegetation greening in a warmer world - Hui Guo; Nan Wei; Zhuoyi Tu; Huiping Huang; Fang Wan; Han Wang; Yanmei Wang; Shengzhi Huang (Agricultural and Forest Meteorology, 2026)

Effects of germplasm type and geographic origin on juice quality of sea buckthorn: A comparative study of physicochemical properties, functional activities, and flavor chemistry - Jingyi Ren; Ting Liu; Saige Zhang; Xingnan Wang; Wenzhi Lei; Yike Han; Guohao Tang; Mengtong Wang; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Chemistry, 2026)

Multi-omics and molecular validation of a novel NRPS biosynthetic gene cluster conferring bio-preservative properties to the probiotic candidate Lactiplantibacillus plantarum 3-1 - Yu Zhang; Tingting Zhang; Jiaqi Gao; Dandan Han; Xinjie Li; Yihang Zhang; Falei Tu; Yanglei Yi; Xin Lü (Food Bioscience, 2026)

Sustainable and durable pure water-fed CO2 electrolysis through cathode cation engineering - Ting-Wei Huang; Tsung-Han Tsai; Kuan-Hung Kuo; Jou-An Hsu; Ding-Huei Tsai; Wei-Ting Tu; Chang-An Chen; Hsin-Liang Kuo; Ming-Kang Tsai; Yung-Tin (Frank) Pan (Chemical Engineering Journal, 2026)

Young adulthood adiposity in relation to all-cause and cause-specific mortality: a prospective study of 0.5 million Chinese adults - Lei Fan; Andri Iona; Shixian Feng; Gang Zhou; Huarong Sun; Pang Yao; Canqing Yu; Yiping Chen; Dianjianyi Sun; Pei Pei; Ling Yang; Mingshu Yan; et al. (Science Bulletin, 2026)

Characterizing China’s post-overbuilding era: cement industry prospects from 2025 to 2100 - Han Tu; Shoujuan Tang; Guangxin Liu; Yang Li; Mingming Hu; Arnold Tukker; Yuping Yan; Lei Shi (Resources, Conservation and Recycling, 2026)

Bio-Fenton reaction system facilitated by the H2O2-producing Desemzia sp. strain C1 degrades sulfonated polyethylene to oxalate - Yongseok Ko; Sunil Ghatge; Youri Yang; Cuong Tu Ho; Dongfei Han; Sujin Lee; Hor-Gil Hur (Journal of Environmental Management, 2026)

A cellulosic waste-upcycled 1T/2H-MoS2/biochar heterostructure for efficient cationic dye adsorption via a multi-anchor chemisorption mechanism - Yifan Lu; Min He; Mingna Ge; Luning Chen; Lin Han; Cong Tu; Bang Yuan; Jie Huang (Journal of Environmental Chemical Engineering, 2026)

Interactions of microbiota during solid-state cereal vinegar fermentation - Dantong Liu; Zhenhua Su; Qi Han; Liting Wang; Linna Tu; Yongjian Yu; Menglei Xia; Yanbing Shen; Yu Zheng; Min Wang (Trends in Food Science & Technology, 2026)

Decoupling of antimony and arsenic migration in a deep neutral legacy Technosol profile with implications for remediation - Yidan Shi; Ling Li; Han Tu; Xuexian Li; Pan Wu (Journal of Environmental Sciences, 2026)

Maximizing CO2 mineralization for a concurrent treatment and resource recovery system of seawater reverse osmosis desalination waste brine through electrochemical generation of alkali - Wei Han Tu; Ger Hui Chan; Shao Ing Wong; Wei Ping Chan; Emiel de Smit; Saifudin Abubakar; Grzegorz Lisak (Water Research, 2026)

Calenduloside E produced by Bifidobacterium animalis B960 increases glibenclamide efficacy and alleviates drug-induced adverse effects in a type 2 diabetes model - Siyuan Shen; Liting Lu; Haiyang Tu; Shuaiming Jiang; Zeng Zhang; Zhe Han; Jiachao Zhang (Science Bulletin, 2026)

High-efficiency two-electron water oxidation tandem system for hydrogen peroxide generation and application - Yonghao Shen; Weiqing Guo; Zhiyong Tu; Qiaozhi Han; Zheshun Ou; Jiating Chen; Ruiting Hu; Zhuofeng Hu (Journal of Environmental Chemical Engineering, 2026)

A central Tibetan highland during the Late Jurassic: Insights from sedimentology, provenance and detrital zircon trace element of the Xueshan Formation in the Qiangtang Basin - Jiawei Zhang; Zhongpeng Han; Yalin Li; Jiarun Tu; Jingen Dai; Xingduo Ma; Zijian Li; Zhihao He; Shuai Li; Wenjun Bi (Global and Planetary Change, 2026)

Redox mediator improves sulfide-autotrophic denitrification under salinity stress via promoting electron transfer and synergistic metabolism - Tong Wang; Jiayi Kou; Huibin Lv; Yaojen Tu; Han Wang; Jian Zhu; Yayi Wang (Environmental Research, 2026)

Sonofoam: An ultrasound-responsive foam for broad pleural coverage and sonoporation-enhanced drug delivery in pleurodesis - Hsin-Yi Lin; Wei-Chih Liao; Yun-Chieh Lin; Hsin-Chin Li; Min-Yu Tsou; Bo-Tai Cheng; Yu-Nan Huang; Ulziijargal Sukhbat; Chun-Yi Chiang; Chi-Fen Chuang; Zong-Han Hsieh; Chih-Yen Tu; et al. (Chemical Engineering Journal, 2026)

Breaking the selectivity dilemma: A 114-fold bee-safe AIE Nanoinsecticide via spontaneous non-covalent orchestration - Han Yan; Bihong Tian; Anjing Liao; Wei Sun; Hong Tu; Yiming Tian; Zhaokai Yang; W.M.W.W. Kandegama; Shengxin Guo; Jian Wu (Chemical Engineering Journal, 2026)

Synergistic effects and decomposition mechanisms of multi-component energetic materials under high-pressure conditions: Improving the ballistic performance of high-chamber-pressure weapons - Pei-chen Han; Jian-Wei Zhang; Ling Chen; Kun Yang; Xin-xin Tu; Shou-yu Wang; Fei-yun Chen; Ping Du (Chemical Engineering Journal, 2026)

Facet-engineered epitaxial TiO2 for early hydrogen detection in lithium-ion battery thermal runaway - Yuanyuan Fu; Liuxi Chen; Weifang Ma; Kaixin Wang; Hanwen Chi; Ni Tu; Jianing Mao; Yunna Guo; Liqiang Zhang; Zhizhen Ye; Zhong-kang Han; Qiyan Wang; et al. (Chemical Engineering Journal, 2026)

Whole-grain black rice diet rewires the single-cell transcriptomic landscape of age-related ovarian decline in mice - Yi-Xuan Tu; Dan-Yang Wang; Jun Ma; Ke-Chun Yu; Sheng-Hui Li; Bo-Han Li; Xin-Yin Deng; Shan Li; Hong-Kai Wang; Tailang Yin; Ling Wang; Zhen-Xia Chen (Science China Life Sciences, 2026)

An enhanced GNSS/INS positioning method with position and attitude constraints in urban environments - Jianhui Cui; Xuan Han; Rufei Liu; Rui Tu; Yan Xiang; Shuangshuang Wu; Zeyu Li; Wenqian Zhou (GPS Solutions, 2026)

Vehicle-borne GNSS/INS integration performance in urban environments with KF-GINS, IGNAV, GINav, PSINS and OB-GINS - Wenqian Zhou; Jianhui Cui; Rui Tu; Rufei Liu; Zeyu Li; Xuan Han (Advances in Space Research, 2026)

Carbon dioxide as the primary greenhouse gas emission in hard clam (Meretrix taiwanica) aquaculture - Yin-Yu Chen; Wei-Sheng Zhang; Chien‑Wei Tu; Bo-Ying Chen; Wen-Ping Cheng; Zhen Hao Liao; Yi-Jung Chen; Meng-Chou Lee; Fan-Hua Nan; Han-Yang Yeh (Aquaculture International, 2026)

Disease outbreaks substantially enhance greenhouse gas emissions from Asian seabass (Lates calcarifer) aquaculture pond - Han-Yang Yeh; Chien-Wei Tu; Yi-Jung Chen; Wen-Ping Cheng; Pei-Yu Shih; Chia-Chia Yu; Wei-Sheng Zhang; Wei-En Hung; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; et al. (Marine Pollution Bulletin, 2026)

Resource and the environmental burdens of excessive construction in China's urban housing sector - Han Tu; Shoujuan Tang; Guangxin Liu; Yang Li; Lei Shi (Resources, Conservation and Recycling, 2026)

Effect of mastication degree and eating rate on in vitro dynamic gastrointestinal digestion of rice - Heng Yu; Jiaxi Tu; Yingying Hou; Hongyi Shi; Jianzhong Han; Weilin Liu (Food Research International, 2026)

Molecular insights into α-Lactalbumin–Chlorogenic acid interaction: Peptide design and anti-inflammatory mechanisms - Shuolei Zheng; Chuanhu Han; Tao Zhang; Xiaoqun Zeng; Weichen Bao; Daodong Pan; Maolin Tu; Zhen Wu (Food Research International, 2025)

Abundant and rare microbial subcommunities exhibit different adaptive strategies to temperature stress in Daqu fermentation - Xing Qin; Qingqing Cao; Mengjing Teng; Ying Han; Fan Yang; Ping Xiang; Huabin Tu (Food Bioscience, 2025)

Temperature-driven deterministic-dominated microbial assembly underpins seasonal divergence in Baijiu high-temperature Daqu - Huabin Tu; Guanyu Zhou; Fanggen Tan; Fan Yang; Ying Han; Jianghua Li; Yanfeng Liu; Yaokang Wu; Jian Chen; Li Wang (Food Bioscience, 2025)

Unveiling the terroir of Chinese baijiu: How altitude shapes the brewing microbiome and flavor chemistry in the Chishui River basin - Siying Yuan; Xiaogang Liu; Rongkun Tu; Dongliang Ren; Lei Yuan; Xiao Han; Shuangping Liu; Jian Mao (Food Bioscience, 2025)

Linking sulfur metabolism to biological nitrogen removal for sustainable wastewater treatment: Microbial synergy perspectives - Tong Wang; Jiayi Kou; Jian Zhu; Yaojen Tu; Han Wang; Xiang Li; Yayi Wang (Bioresource Technology, 2025)

Influence of Layout on Offshore Wind Farm Efficiency and Wake Characteristics in Turbulent Environments - Guanyu Wang; Junnan Huang; Zhihao Zhang; Kang Chen; Zhuang Shen; Jiahuang Tu; Zhaolong Han (Journal of Marine Science and Engineering, 2025)
Mitigating wake effects between wind turbines is crucial for enhancing the overall output power of offshore wind farms. Therefore, optimizing turbine spacing and layout under turbulent conditions is essential. This study employs the NREL-5 MW wind turbine model to investigate the efficiency of a 3 × 3 wind farm. This research focuses on the influence of turbine spacing and layout on wake field distribution and output power characteristics under different turbulence intensities. A key innovation is the application of entropy production theory to quantify energy dissipation and wake recovery, providing a deeper understanding of the underlying mechanisms in energy losses. This research also introduces fatigue analysis based on the Damage Equivalent Load (DEL) method, revealing that staggered layouts significantly reduce cyclic loads and extend turbine lifespan. The results indicate that modifying the layout is a more effective strategy for enhancing the total power output of the wind farm, which proves to be more effective than altering the turbulence intensity. Specifically, staggered layout I (with a downstream stagger of 1.0 rotor diameter (D)) increases total output power by 28.76% (to 36.84 MW) and causes a 16.38% surge in power when the spacing increases to 5D. Expanding the wind turbine spacing mitigates wake interaction, resulting in a dramatic 59.84% power recovery for downstream wind turbines. The wind turbine’s lifespan is extended as a result of fatigue loads on the root bending moment being substantially reduced by the staggered layout, which alters the wake structure and stress distribution. The entropy production analysis shows that regions with high entropy production are primarily concentrated near the rotor and within the wake shear layer. The energy dissipation is substantially reduced in the case of staggered layout. These findings provide valuable guidance for the aerodynamic optimization and long-term operation design of large-scale wind farms, contributing to improved energy efficiency and reduced maintenance costs.

Quantitative analysis of seven free short-chain fatty acids in infant formula using GC–MS/MS - Yunxiao Zhu; Yang Liu; Qiu Sun; Jia Chen; Mengling Tu; Yehua Han; Xianjiang Li (Food Chemistry, 2025)

Isolation of largemouth bass virus (LMBV) and dominant immunogenic epitope screening of the major capsid protein of LMBV - Jie Leng; Ling-Yun Lin; Yun-Yao Tu; Cheng-Ke Zhu; Qun Lu; Ming-Ji Lv; Tao He; Jian-Yong Hu; Zhao-Fang Han; Song Zhu (Fish & Shellfish Immunology, 2025)

Assessing the welfare of smallholder pigs in Vietnam using a pilot protocol - Sinh Dang-Xuan; Le Thi Thanh Huyen; Tu-Quynh Ha; Do Van Duc; Le Tien Dung; Han Anh Tuan; Fred Unger; Rebecca Doyle; Jenny-Ann Toribio (Tropical Animal Health and Production, 2025)
Smallholder pig farms are an important feature of pork supply in Asia, and these farming approaches present unique management considerations. This survey was conducted to pilot a welfare assessment protocol and to investigate smallholder pig management and welfare at two sites in Vietnam, one with 55 farms raising predominantly indigenous pigs (the Da Bac site) and the other 55 farms raising predominantly non-indigenous pigs (the Lac Son site). Farmers at both sites kept small numbers of confined pigs, with more keeping sows in Da Bac and some keeping only grower pigs in Lac Son. Via an interview and pig observation, data on 18 welfare measures were recorded for adult pigs, suckling piglets and grower pigs. Pigs on > 90% of farms did not exhibit panting, tail biting, scouring, negative social behaviour, stereotypic behaviour, coughing or lameness demonstrating adequate welfare for these welfare measures. However, all pigs on > 50% of farms had restricted access to drinking water at both sites, and pigs often displayed fear of humans in the Da Bac site. The body condition of most pigs was thin or very thin among the sows on 31% of farms and among the grower pigs on 32% of farms. This pilot proved that the welfare assessment protocol is feasible and provided lessons for its future use in other low-to-middle income countries. It also found that low-cost interventions are urgently needed to address water access and undernutrition in order to improve the welfare of smallholder pigs and the production of these farms.

Temporal variability of greenhouse gas fluxes in monoculture of tilapia in ponds - Yi–Jung Chen; Han–Yang Yeh; Chien-Wei Tu; Yu-Ru Lin; Zhen Hao Liao; Wen-Chen Chou; Hsiao-Chun Tseng; Ruei-Feng Shiu; Tzu-Ning Teng; Meng–Chou Lee; Fan–Hua Nan (Aquaculture International, 2025)

Utilizing UAV-based high-throughput phenotyping and machine learning to evaluate drought resistance in wheat germplasm - Xiaojing Zhu; Xin Liu; Qian Wu; Mengshi Liu; Xueli Hu; Hui Deng; Yun Zhang; Yunfeng Qu; Baoqi Wang; Xiaoman Gou; Qiongge Li; Changsheng Han; et al. (Computers and Electronics in Agriculture, 2025)

The influence of water flow disturbance form on the granulation of algae sludge: Granulation property, treatment effect and algae biological structure - Peng-fei Yu; Ao Wang; Hai-wen Sun; Ding Wang; Xing-guan Ma; Yu-jia Wang; Bo-mei Hu; Li-yao Han; Yu-bo Fu; Dian-lin Jiang; Shi-gang Tu (Journal of Water Process Engineering, 2025)

Global terrestrial evaporation from physically-based, calibration-free complementary relationship - Zhuoyi Tu; Yuting Yang; Fangzheng Ruan; Changming Li; Juntai Han; Jinghua Xiong (Journal of Hydrology, 2025)

Interfacial engineering with moderate sodiophilic zinc-nitrogen sites for highly reversible anode-free sodium metal batteries - Ziyu Chen; Chen Zhang; Han Fu; Dongxu Zhou; Ying Xu; Jiawen Chen; Yu Zhong; Xiuli Wang; Changdong Gu; Jiangping Tu (Chemical Engineering Journal, 2025)

Enhancement of CO2 tolerance of BaCeO3 by B-site regulation for protonic ceramic electrolytes - Zhiwei Peng; Ye Han; Xiangnan Wang; Huiying Qi; Baofeng Tu; Chunyan Xiong; Haoyu Zheng; Peng Qiu (Chemical Engineering Journal, 2025)

Integrated source apportionment and risk assessment prioritizes heavy metal control at an abandoned antimony smelter - Xiao-Hong Ma; Zhuan-Ling Shao; Yu-Han Wang; Wei-Di Tu; Li-Bang Ma; Jiao Wang (Environmental Geochemistry and Health, 2025)

Succession of biological soil crusts modifies patterns of soil eukaryotic communities along a precipitation gradient - Lin Xu; Yongping Kou; Xiangzhen Li; Chaonan Li; Jiabao Li; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengmin You; Han Li; Sining Liu; Yang Liu; et al. (Applied Soil Ecology, 2025)

Fish Swimming Behavior and Strategies Under Different Hydrodynamic Conditions in Fishways with Various Vertical Slot Configurations - Lijian Ouyang; Dongqiu Li; Shihao Cui; Xinyang Wu; Yang Liu; Xiaowei Han; Shengzhi Zhou; Gang Xu; Xinggang Tu; Kang Chen; Carlo Gualtieri; Weiwei Yao (Fishes, 2025)
Vertical slot fishways are a crucial measure to mitigate the blockage of fish migration caused by hydraulic engineering infrastructures, but their passage efficiency is often hindered by the complex interactions between fish behavior and hydrodynamic conditions. This study combines computational fluid dynamics (CFD) simulations with behavioral laboratory experiments to identify the hydrodynamic characteristics and swimming strategies of three types of fishways—Central Orifice Vertical Slot (COVS), Standard Vertical Slot (SVS), and L-shaped Vertical Slot (LVS)—using the endangered species Schizothorax prenanti from the upper Yangtze River as the study subject. The results revealed that (1) a symmetric and stable flow field was formed in the COVS structure, yet the passage ratio was the lowest (50%); in the SVS structure, high turbulent kinetic energy (peak of 0.03 m2/s2) was generated, leading to a significant increase in the fish’s tail-beat angle and amplitude (p 0.68). The LVS structure achieved the highest passage ratio and shortest transit time for Schizothorax prenanti, demonstrating its superior functionality for upstream migration. This design balances hydrodynamic complexity with low-turbulence refuge zones, providing a practical solution for eco-friendly fishways.

Mechanistic insights into ozone-induced asthma exacerbation: role of oxidative stress and IL-33 - Xinyi Fang; Bin Pan; Yuanting Xie; Wenpu Shao; Jingyu Li; Dongyang Han; Xiaoqing Hong; Wenyue Tu; Yifan Zhao; Jiaojiao Wu; Yaning Zhu; Yubin Zhang; et al. (Journal of Hazardous Materials, 2025)

Location-optimized remediation measures for soil multifunctionality and carbon sequestration of saline-alkali land in China - Zhaoqiang Han; Yi Leng; Zhe Xu; Longping Tu; Chao Wang; Shuqing Li; Shuang Wu; Yawen Huang; Shuwei Liu; Jinyang Wang; Philippe Ciais; Ruoya Ma; et al. (Journal of Cleaner Production, 2025)

Celecoxib as a potential treatment for hepatocellular carcinoma in populations exposed to high PFAS levels - Boshi Sun; Yuqiao Zhao; Shifeng Yang; Xiaodong Li; Nana Li; Yujie Wang; Qixiang Han; Xuyun Liu; Qiushi Tu; Jie Zheng; Xinyu Zhang (Journal of Hazardous Materials, 2025)

The synergistic effects of NaOH and NaCl on the gel properties, digestive characteristics, and product quality of salted preserved egg white - Sizhen Yan; Tianfeng Han; Hui Xue; Ping Wang; Yonggang Tu; Yan Zhao (Food Research International, 2025)

Rapid detection of the viability of naturally aged maize seeds using multimodal data fusion and explainable deep learning techniques - He Li; Yilin Mao; Yanan Xu; Keling Tu; Han Zhang; Riliang Gu; Qun Sun (Food Chemistry, 2025)

Metabolomics and volatilomics unravel the signature of pivotal bioactive metabolites in sea buckthorn juice and pomace under hydrolysis of cellulase and pectinase - Xingnan Wang; Jingyi Ren; Yanting Chen; Ting Liu; Hongcai Li; Wenzhi Lei; Yike Han; Shiqi Li; Xiaoning Tu; Bin Zhang; Guangquan Liu; Zhenpeng Gao (Food Bioscience, 2025)

Exploring the Potential of Purple Non-Sulfur Bacteria Strains A3-5 and F3-3 in Sustainable Agriculture: A Study on Nutrient Solubilization, Plant Growth Promotion, and Acidic Stress Tolerance - Jun-Yu Wu; Han-Wei Chen; Laurence Shiva Sundar; Yuan-Kai Tu; Yun-Yang Chao (Journal of Soil Science and Plant Nutrition, 2025)

Mineral fertilizer substitution and application of Bacillus velezensis SQR9 reduced nitrogen-oxide emissions in tropical vegetable fields - Wei Tian; Feilong Liang; Longping Tu; Zhe Xu; Rong Li; Ruoya Ma; Yawen Huang; Shuang Wu; Shuqing Li; Jinyang Wang; Shuwei Liu; Zhaoqiang Han; et al. (Agriculture, Ecosystems & Environment, 2025)

Feasibility of gold leaching from waste printed circuit boards with an airlift bioreactor applying the condensed distillers solubles as a microbial nutrient and its recovery by reduction - Duy Tho Tran; Ngoc Tu Trinh Tran; Xiaoyu Lin; Jong-won Choi; Minhee Han; Myung-Hee Song; Yeoung-Sang Yun (Journal of Environmental Management, 2025)

Low perception of climate change by farmers and herders on Tibetan Plateau - Jiawei Yi; Yuan Tian; Nicholas P. Simpson; Yunyan Du; Ting Ma; Chengqun Yu; Talbot M. Andrews; Tao Pei; Xinjie Zha; Chenghu Zhou; Wei Sun; Shaowei Li; et al. (Global Environmental Change, 2025)

GNSS-IR water level monitoring for complex environments: Application to Kalabeily Reservoir in Xinjiang, China - Peiyuan Wang; Rui Tu; Xiaolei Wang; Junqiang Han; Junjian Zhang; Fang Cheng; Xiaochun Lu (Advances in Space Research, 2025)

Hydrodynamic Study of a Fall Pipe Rock Dumping System - Mingjiu Zuo; Xinyi Zhou; Haiwen Tu; Zehui Liang; Yan Wei; Kai Xia; Haodi Zhu; Haibin Han; Jiayi Su; Fengzhong Qu (Journal of Marine Science and Engineering, 2025)
The fall pipe rock dumping technique is extensively employed to create protection embankments around submarine cables, mitigating distortion and breakage resulting from bottom scouring. During the rock dumping operation, intricate interactions among the pipeline, rocks, and water currents can affect the stability and efficiency of the fall pipe system. This research proposed a method employing the fluid–structure interaction to analyze the interactions between the pipeline, rocks, and water currents. The paper begins with the design of an innovative fall pipe rock dumping system and presents a theoretical analysis of the applied model testing approach. The simulation parameters were determined according to the geometric, Froude, and Strouhal similarity criteria. A thorough numerical analysis was performed to investigate the hydrodynamic properties of the rockfall pipeline under fluid–structure interaction. The research examined the settling of rocks during rockfall, along with the forces and movements associated with the deposition process. The results show that the rockfall pipeline experienced vortex-induced vibrations (VIVs) caused by ocean currents during operation. The maximum settling velocity of the rocks throughout the rockfall process reached 2.2 m/s, with a final stable velocity of 1.5 m/s. These simulation results offer critical insights for improving the design and functionality of the rockfall pipeline, thereby enhancing the protection of underwater infrastructure.

Cumulative impact of human activities on hydro-sediment dynamics and morphodynamics in the highly altered Yangtze Estuary - Xiangju Han; Daidu Fan; Ju Huang; Junbiao Tu; Lingpeng Meng; Shenliang Chen (Journal of Hydrology, 2025)

Rapid detection of corn seed turtle cracks based on transmitted light image and deep learning method - He Li; Yun Hao; Weifeng Wu; Keling Tu; Yanan Xu; Han Zhang; Danyang Zhang; Mingliu Li; Riliang Gu; Qun Sun (Computers and Electronics in Agriculture, 2025)

Climate outweighs fertiliser effects on soil phoD-harbouring communities in agroecosystems - Lin Xu; Yongping Kou; Qian Mao; Xiangzhen Li; Chaonan Li; Bo Tu; Jiabao Li; Lihua Tu; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Soil Biology and Biochemistry, 2025)

Development of zebrafish (Danio rerio) mesh-type model at multi-life stages and Monte Carlo simulations of dosimetric parameters - Huiyuan Xue; Wenxing Xu; Xiaotong Gao; Han Gao; Xinjie Wang; Jin Gao; Yidi Wang; Kaijin Yan; Tao Wu; Jiahao Guo; Binquan Niu; Mingxu Zheng; et al. (Journal of Environmental Radioactivity, 2025)

Comprehensive analysis of spatiotemporal heterogeneity reveals the effects of physicochemical and biological factors on temperature rise during the Moutai-flavor Baijiu stacking fermentation process - Yuanbu Li; Xing Qin; Xianglian Zeng; Menglin She; Liangqiang Chen; Jianjun Lu; Ying Han; Fan Yang; Huabin Tu; Hai Du; Yan Xu (Chemical Engineering Journal, 2025)

Degradation of pharmaceuticals and personal care products (PPCPs) in municipal wastewater by white rot fungi: Neutral environment exploitation and degradation mechanisms - Yizhou Tu; Liqin Han; Xiaolu Ding; Xingqi Zhu; Guizhou Xu; Xianchuan Xie; Qing Zhou; Chendong Shuang; Aimin Li (Chemical Engineering Journal, 2025)

FSD1 inhibits glioblastoma diffuse infiltration through restriction of HDAC6-mediated microtubule deacetylation - Dake Xiao; Haowen Ran; Lishu Chen; Yuanyuan Li; Yan Cai; Songyang Zhang; Qinghui Qi; Huiran Wu; Cheng Zhang; Shuailiang Cao; Lanjuan Mi; Haohao Huang; et al. (Science China Life Sciences, 2025)
The infiltration of glioblastoma multiforme (GBM) is predominantly characterized by diffuse spread, contributing significantly to therapy resistance and recurrence of GBM. In this study, we reveal that microtubule deacetylation, mediated through the downregulation of fibronectin type III and SPRY domain-containing 1 (FSD1), plays a pivotal role in promoting GBM diffuse infiltration. FSD1 directly interacts with histone deacetylase 6 (HDAC6) at its second catalytic domain, thereby impeding its deacetylase activity on α-tubulin and preventing microtubule deacetylation and depolymerization. This inhibitory interaction is disrupted upon phosphorylation of FSD1 at its Ser317 and Ser324 residues by activated CDK5, leading to FSD1 dissociation from microtubules and facilitating HDAC6-mediated α-tubulin deacetylation. Furthermore, increased expression of FSD1 or interference with FSD1 phosphorylation reduces microtubule deacetylation, suppresses invasion of GBM stem cells, and ultimately mitigates tumor infiltration in orthotopic GBM xenografts. Importantly, GBM tissues exhibit diminished levels of FSD1 expression, correlating with microtubule deacetylation and unfavorable clinical outcomes in GBM patients. These findings elucidate the mechanistic involvement of microtubule deacetylation in driving GBM cell invasion and offer potential avenues for managing GBM infiltration.

A long-term stable solid-state nanopore for the dynamic monitoring of DNA synthesis - Han Yan; Tianyu Chen; Gang Hu; Jie Ma; Lingzhi Wu; Jing Tu (Analytica Chimica Acta, 2025)

Possible role of autophagy in microbial volatile pollutant-induced starch degradation and expression of hypoxia responsive genes - Chung-Chih Huang; Ching-Han Chang; Tu-Trinh Thi Truong; Wu-Guei Wang; Che-Hui Lin; Chih-Yun Chiang; Iwai Obayashi; Hao-Jen Huang (Environmental Pollution, 2025)

Seipin Deficiency Impairs Motor Coordination in Mice by Compromising Spinal Cord Myelination - Hong Chen; Wenru Wang; Wenli Cui; Chuanyun Tu; Yuanyuan Han; Chengwu Zhang; Liu Yang; Xintao Huang; Qin Zhang; Li Lu (NeuroMolecular Medicine, 2025)

Bismuth/manganese-doped carbon dots in calcium phosphate matrix: Dynamic conformational nanoparticles enhancing tumor accumulation, deep penetration, and radiosensitivity - Jiahao Liu; Qingnian Li; Hanyu Tu; Jie Feng; Xiaofei Fan; Ze Mi; Hongpei Han; Xiaoqian Ma; Qi Liang; Zheng Zhang; Hongshuai Hou; Pengfei Rong; et al. (Chemical Engineering Journal, 2025)

Multi objective motion planning of fruit harvesting manipulator based on improved BIT* algorithm - Peifeng Ma; Aibin Zhu; Yihao Chen; Yao Tu; Han Mao; Jiyuan Song; Xin Wang; Sheng Su; Dangchao Li; Xia Dong (Computers and Electronics in Agriculture, 2024)

26Al/10Be burial dating of Majuangou sites in Nihewan Basin, northern China - Hua Tu; Xinfeng Zhang; Lan Luo; Fei Xie; Fei Han; Zhongping Lai; Darryl E. Granger; Guanjun Shen (Quaternary Science Reviews, 2024)

Uncovering the effects and mechanisms of tea and its components on depression, anxiety, and sleep disorders: A comprehensive review - Ziyi Han; Leyu Wang; Huanqing Zhu; Youying Tu; Puming He; Bo Li (Food Research International, 2024)

Cooperative interaction between Pediococcus and Bacillus communities as a key factor in the high-temperature Thermal differentiation of Daqu - Huabin Tu; Guanyu Zhou; Jianjun Lu; Fanggen Tan; Ying Han; Fan Yang; Hai Du; Yanfeng Liu; Jianghua Li; Li Wang; Jian Chen (Food Bioscience, 2024)

Suppressing dendrite growth through the design of glassy sulfide for all-solid-state lithium metal batteries - Juner Kuang; Han Su; Yu Zhong; Chengao Zhou; Xiuli Wang; Jiangping Tu (Chemical Engineering Journal, 2024)

Hypoxia drives estrogen receptor β-mediated cell growth via transcription activation in non-small cell lung cancer - Qi Su; Kun Chen; Jiayan Ren; Yu Zhang; Xu Han; Sze Wei Leong; Jingjing Wang; Qing Wu; Kaihui Tu; Ammar Sarwar; Yanmin Zhang (Journal of Molecular Medicine, 2024)

Non-coding RNA notations, regulations and interactive resources - Mengwei Cheng; Yinhuan Zhu; Han Yu; Linlin Shao; Yiming Zhang; Lanxing Li; Haohong Tu; Luyao Xie; Haoyu Chao; Peijing Zhang; Saige Xin; Cong Feng; et al. (Functional & Integrative Genomics, 2024)

Acquired thermotolerance in Crassostrea angulata: Effects of priming temperature, recovery temperature and duration on the survival and expression of HSP genes - Yiheng Song; Ziqiang Han; Zuoliang Lu; Yanle Jiang; Yikun He; Kang Tu; Huayong Que (Aquaculture, 2024)

Characteristics of surface microlayer film under different freshwater environments: Physical, chemical, and biological properties - Yuankun Yang; Tian Ma; Shu Chen; Han Song; Lunzhen Li; Yu He; Tao Song; Qiuhong Zhou; Weiguo Tu (Process Safety and Environmental Protection, 2024)

Dynamics of a single cavitation bubble near a cylindrical blind hole - Doo-Woon Han; Seong-Ho Park; Nguyen Duy-Trong; Van-Tu Nguyen; Hemant Sagar; Ould El Moctar; Thanh-Hoang Phan; Warn-Gyu Park (Ocean Engineering, 2024)

Revisiting the estimation indicator for HONO emissions from light-duty vehicles - Xinping Yang; Mingliang Fu; Songdi Liao; Zhipeng Tu; Weijie Feng; Yunjing Wang; Han Jiang; Qili Tian; Hang Yin; Junyu Zheng; Yan Ding (Journal of Hazardous Materials, 2024)

Constraining the evaporative loss of zinc during impact processes using terrestrial impact glasses - Zheng-Yu Long; Frédéric Moynier; Marine Paquet; James M.D. Day; Linru Fang; Tu-Han Luu; Dimitri Rigoussen; Kun-Feng Qiu; Jun Deng; Christian Koeberl (Earth and Planetary Science Letters, 2024)

Investigating the expansion behavior of silicon nitride nanopores - Han Yan; Gang Hu; Ziqing Wu; Tianyu Chen; Lingzhi Wu; Zuhong Lu; Jing Tu (Chemical Engineering Journal, 2024)

Natural shading is helpful but not sufficient for mitigating warming in green sea turtle nests in the tropical South China Sea - Tsung-Han Liu; Ming-Shiou Jeng; Chan-Yuan David Lee; Chih-Wei Tu; Po-Hsiung Lin; Chaolun Allen Chen; Chia-Ying Ko (Biological Conservation, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Effect of pH, protein/polysaccharide ratio and preparation method on the stability of lactoferrin-polysaccharide complexes - Qi Meng; Hanyun Jiang; Jiaxi Tu; Yimeng He; Zijun Zhou; Ruijie Wang; Weiping Jin; Jianzhong Han; Weilin Liu (Food Chemistry, 2024)

In situ construction of ether-based composite electrolyte with stable electrode interphase for high-performance solid state lithium metal battery - Yixiao Zhang; Xue Ye; Han Fu; Yu Zhong; Xiuli Wang; Changdong Gu; Jiangping Tu (Chemical Engineering Journal, 2024)

Capsaicin reduces blood glucose and prevents prostate growth by regulating androgen, RAGE/IGF-1/Akt, TGF-β/Smad signalling pathway and reversing epithelial-mesenchymal transition in streptozotocin-induced diabetic mice - Hui Sun; ZiTong Wang; BingHua Tu; ZiChen Shao; YiDan Li; Di Han; YinJie Jiang; Peng Zhang; WeiChang Zhang; YunYan Wu; XiaoMing Wu; Chi-Ming Liu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

Separation of ovomucin from duck egg white and its “acid-tight /alkali-loose” self-supporting gel properties under different pH - Yao Yao; Yucheng Zhong; Han Li; Tiantian Liu; Na Wu; Shuping Chen; Lilan Xu; Yan Zhao; Yonggang Tu (Food Hydrocolloids, 2024)

Water quality assessment and its pollution source analysis from spatial and temporal perspectives in small watershed of Sichuan Province, China - Tao Song; Weiguo Tu; Mingyue Su; Han Song; Shu Chen; Yuankun Yang; Min Fan; Xuemei Luo; Sen Li; Jingjing Guo (Environmental Monitoring and Assessment, 2024)

Research on Aerodynamic Characteristics of Three Offshore Wind Turbines Based on Large Eddy Simulation and Actuator Line Model - Chen Fu; Zhihao Zhang; Meixin Yu; Dai Zhou; Hongbo Zhu; Lei Duan; Jiahuang Tu; Zhaolong Han (Journal of Marine Science and Engineering, 2024)
Investigating the aerodynamic performance and wake characteristics of wind farms under different levels of wake effects is crucial for optimizing wind farm layouts and improving power generation efficiency. The Large Eddy Simulation (LES)–actuator line model (ALM) method is widely used to predict the power generation efficiency of wind farms composed of multiple turbines. This study employs the LES-ALM method to numerically investigate the aerodynamic performance and wake characteristics of a single NREL 5 MW horizontal-axis wind turbine and three such turbines under different wake interaction conditions. For the single turbine case, the results obtained using the LES-ALM method were compared with the existing literature, showing good agreement and confirming its reliability for single turbine scenarios. For the three-turbine wake field problem, considering the aerodynamic performance differences under three cases, the results indicate that spacing has a minor impact on the power coefficient and thrust coefficient of the middle turbine but a significant impact on the downstream turbine. For staggered three-turbine arrangements, unilateral turbulent inflow to the downstream turbine causes significant fluctuations in thrust and torque, while bilateral turbulent inflow leads to more stable thrust and torque. The presence of two upstream turbines causes an acceleration effect at the inflow region of the downstream single turbine, significantly increasing its power coefficient. The findings of this study can provide methodological references for reducing wake effects and optimizing the layout of wind farms.

Wave, flow, and suspended sediment dynamics under strong winds on a tidal beach - Lingpeng Meng; Junbiao Tu; Xiaodong Wu; Sha Lou; Jun Cheng; Sergey Chalov; Xiangju Han; Daidu Fan (Estuarine, Coastal and Shelf Science, 2024)

Influence of Pteris vittata-maize intercropping on plant agronomic parameters and soil arsenic remediation - Tianying Wan; Xiangwei Dong; Lihua Yu; Dandan Li; Haozhan Han; Shuxin Tu; Jin Wan (Chemosphere, 2024)

Effects of combined treatment with hydrogen-rich electrolyzed water and tea polyphenols on oxidative stress, intestinal injury and intestinal flora disruption in heat-stressed mice - Yao Zang; Beibei Zhang; Guosheng Zhang; Jie Hu; Dengqun Shu; Jiahong Han; Mengzhen Hu; Mingming Tu; Wenduo Qiao; Renxin Liu; Yitian Zang (Journal of Thermal Biology, 2024)

Revealing the mechanism of Ce promoter in modulating product distribution of CO2 hydrogenation over Fe-based catalysts - Yanjia Guo; Lingyu Jia; Zhenzhou Zhang; Mengze Gong; Shanshan Dang; Yanqiang Huang; Xinhua Gao; Weifeng Tu; Yi-Fan Han (Chemical Engineering Journal, 2024)

Consistent community assembly but contingent species pool effects drive β‐diversity patterns of multiple microbial groups in desert biocrust systems - Lin Xu; Xiangzhen Li; Xin Tang; Yongping Kou; Chaonan Li; Jiabao Li; Minjie Yao; Bingchang Zhang; Lixia Wang; Hongwei Xu; Chengming You; Han Li; et al. (Molecular Ecology, 2024)
One of the key goals of ecology is to understand how communities are assembled. The species co‐existence theory suggests that community β‐diversity is influenced by species pool and community assembly processes, such as environmental filtering, dispersal events, ecological drift and biotic interactions. However, it remains unclear whether there are similar β‐diversity patterns among different soil microbial groups and whether all these mechanisms play significant roles in mediating β‐diversity patterns. By conducting a broad survey across Chinese deserts, we aimed to address these questions by investing biological soil crusts (biocrusts). Through amplicon‐sequencing, we acquired β‐diversity data for multiple microbial groups, that is, soil total bacteria, diazotrophs, phoD ‐harbouring taxa, and fungi. Our results have shown varying distance decay rates of β‐diversity across microbial groups, with soil total bacteria showing a weaker distance‐decay relationship than other groups. The impact of the species pool on community β‐diversity varied across microbial groups, with soil total bacteria and diazotrophs being significantly influenced. While the contributions of specific assembly processes to community β‐diversity patterns varied among different microbial groups, significant effects of local community assembly processes on β‐diversity patterns were consistently observed across all groups. Homogenous selection and dispersal limitation emerged as crucial processes for all groups. Precipitation and soil C:P were the key factors mediating β‐diversity for all groups. This study has substantially advanced our understanding of how the communities of multiple microbial groups are structured in desert biocrust systems.

Numerical analysis of coarse particle two-phase flow in deep-sea mining vertical pipe transport with forced vibration - Chuyi Wan; Shengpeng Xiao; Dai Zhou; Hongbo Zhu; Yan Bao; Tingping Li; Jiahuang Tu; Muwanguzi Stephen Kyazze; Zhaolong Han (Ocean Engineering, 2024)

A novel bifunctional particle electrode with abundant Fe/Fe3C and Fe-N-C sites to enhance the performance of electro-Fenton in degrading organic pollutant - Junjie Cheng; Xinman Tu; Li Zhang; Mingzhu Han; Rentao Zhou; Shaohua Luo; Honghu Zeng; Tingting Li; Jianping Zou (Journal of Environmental Chemical Engineering, 2024)

Strategy strengthens structural identification through hyphenating full collision energy ramp-MS2 and full exciting energy ramp-MS3 spectra: An application for metabolites identification of rosmarinic acid - Ke Zhang; Han Li; Jingjing Shi; Wenjing Liu; Yitao Wang; Pengfei Tu; Jun Li; Yuelin Song (Analytica Chimica Acta, 2024)

Reclaimed seawater discharge – Desalination brine treatment and resource recovery system - Wei Han Tu; Ya Zhao; Wei Ping Chan; Grzegorz Lisak (Water Research, 2024)

Pregnancy maintenance and fetal loss assessment in Holstein cows through analyzing pregnancy-associated glycoproteins in milk - Ming-Kuew Yang; Ruei-Han Yeh; Chia-Jung Lee; Yi-Hsin Yeh; Yi-Hsuan Chen; Thomas Banhazi; Po-An Tu (Theriogenology, 2024)

Polyolefin-derived substrate-grown carbon nanotubes as binder-free electrode for hydrogen evolution in alkaline media - XinYi Wu; Wei Han Tu; Andrei Veksha; Wenqian Chen; Grzegorz Lisak (Chemosphere, 2024)

Effects of light spectra on the ovarian maturation and maternal immunity in the little yellow croaker (Larimichthys polyactis) - Ming Ming Han; Wei Zhan; Xiao Liang; Dan Dan Guo; Wan Tu Xu; Bao Lou (Aquaculture, 2024)

An optimization framework for wind farm layout design using CFD-based Kriging model - Zhenfan Wang; Yu Tu; Kai Zhang; Zhaolong Han; Yong Cao; Dai Zhou (Ocean Engineering, 2024)

Efficient electron transport between NiO/Fe2O3 by loading amorphous carbon improves photocatalytic degradation property - Weihang Han; Jingxuan Shou; Shouxin Zhu; Xuewei Tu; Yutong Chen; Can Sun; Yurong Chang; Hui Zheng (Journal of Environmental Chemical Engineering, 2024)

Tea seed saponins ameliorate cyclophosphamide-induced intestinal injury, immune disorder and gut microbial dysbiosis in mice - Shuna Chen; Jiaxin Kang; Huanqing Zhu; Ziyi Han; Leyu Wang; Kaixi Wang; Junsheng Liu; Yuanyuan Wu; Puming He; Youying Tu; Bo Li (Food Bioscience, 2024)

Metal-organic framework-polymer complex-derived single-atomic oxygen reduction catalyst for anion exchange membrane fuel cells - Quoc Hao Nguyen; Vo Dinh Cong Tinh; Sion Oh; Toan Minh Pham; Thach N. Tu; Dukjoon Kim; Jonghee Han; Kyungmin Im; Jinsoo Kim (Chemical Engineering Journal, 2024)

Green Synthesis of Carbon Aerogel Derived from Lotus Root for the Removal of Ciprofloxacin, Oil, Organic Solvents, and Supercapacitor Applications - Mai Thanh Phong; Phan Minh Tu; Nguyen Duy Hai; Nguyen Thanh Hoai Nam; Vo Minh Quan; Tran Ngoc Son; Tong Hoang Lin; Le Gia Han; Nguyen Truong Son; Nguyen Huu Hieu; Ton That Buu (Water, Air, & Soil Pollution, 2024)

Fani Maoré, a new “young HIMU” volcano with extreme geochemistry - Catherine Chauvel; Edward C. Inglis; Pamela Gutierrez; Tu-Han Luu; Pierre Burckel; Pascale Besson (Earth and Planetary Science Letters, 2024)

Climate match is key to predict range expansion of the world's worst invasive terrestrial vertebrates - Yuanbao Du; Xuyu Wang; Sadia Ashraf; Weishan Tu; Yonghong Xi; Ruina Cui; Shengnan Chen; Jiajie Yu; Lixia Han; Shimin Gu; Yanhua Qu; Xuan Liu (Global Change Biology, 2024)
Understanding the determinants of the range expansion of invasive alien species is crucial for developing effective prevention and control strategies. Nevertheless, we still lack a global picture of the potential factors influencing the invaded range expansion across taxonomic groups, especially for the world's worst invaders with high ecological and economic impacts. Here, by extensively collecting data on 363 distributional ranges of 19 of world's worst invasive terrestrial vertebrates across 135 invaded administrative jurisdictions, we observed remarkable variations in the range expansion across species and taxonomic groups. After controlling for taxonomic and geographic pseudoreplicates, model averaging analyses based on generalized additive mixed‐effect models showed that species in invaded regions having climates more similar to those of their native ranges tended to undergo a larger range expansion. In addition, as proxies of propagule pressure and human‐assisted transportation, the number of introduction events and the road network density were also important predictors facilitating the range expansion. Further variance partitioning analyses validated the predominant role of climate match in explaining the range expansion. Our study demonstrated that regions with similar climates to their native ranges could still be prioritized to prevent the spread of invasive species under the sustained global change.

Novel multienzyme cascade for efficient synthesis of d-allulose from inexpensive sucrose - Ruizhi Han; Wenyu Tu; Shuangyu Liu; Yu Ji; Ulrich Schwaneberg; Yuanyi Guo; Ye Ni (Food Bioscience, 2023)

Enhancing interfacial stability in sulfide all-solid-state batteries through surface dual-doping of Zr and F in Ni-rich cathodes - Daoyan Feng; Yu Liu; Chen Zhao; Han Su; Xia Kong; Yu Zhong; Junzhang Wang; Zhou Xu; Xiuli Wang; Xingzhong Guo; Jonghee Lee; Jiangping Tu (Chemical Engineering Journal, 2023)

Chemical constituents from Vitex negundo var. cannabifolia (Sieb. et Zucc.) Hand.-Mazz. (Lamiaceae) and their chemotaxonomic significance - Muhammad Aurang Zeb; Peng-Yun Yang; De-Wen Bi; Wen-Chao Tu; Xiao-Li Li; Rui-Han Zhang; Xing-Jie Zhang; Wei-Lie Xiao (Biochemical Systematics and Ecology, 2023)

Uncovering molecular mechanisms involved in microbial volatile compounds-induced stomatal closure in Arabidopsis thaliana - Tu-Trinh Thi Truong; Chi-Chou Chiu; Jing-Yu Chen; Pei-Yu Su; Tri-Phuong Nguyen; Ngoc-Nam Trinh; Tetsuro Mimura; Ruey-Hua Lee; Ching-Han Chang; Hao-Jen Huang (Plant Molecular Biology, 2023)

Natural revegetation has dominated annual runoff reduction since the Grain for Green Program began in the Jing River Basin, Northwest China - Yipeng Yu; Pengtao Yu; Yanhui Wang; Yanfang Wan; Bin Wang; Xinsheng Han; Xinwu Tu; Jiamei Li; Lihong Xu; Xiao Wang; Zebin Liu (Journal of Hydrology, 2023)

Tailored production and application of biochar for tar removal - Alba Dieguez-Alonso; Tu-Lien Eliane Vu-Han; Hernán Almuina-Villar; Juan Jesús Rico Fuentes; Liane Hilfert; Andrea Dernbecher; José María de la Rosa; Frank Behrendt (Fuel, 2023)

Effects of anti-pull ties on the bearing behaviors of shallow tunnel-type anchorages in soft rock - Ya-feng Han; Xin-rong Liu; Erdi Abi; Yi-liang Tu; Bin Xu; Xiao-han Zhou; Zhi-yun Deng; Zhong-hao Wang (Journal of Mountain Science, 2023)

Aerodynamic characterization of two tandem wind turbines under yaw misalignment control using actuator line model - Yu Tu; Kai Zhang; Zhaolong Han; Dai Zhou; Onur Bilgen (Ocean Engineering, 2023)

Numerical analysis of a modified combined volumetric filtered concentrating PV/T system using MCRT and FVM coupled method - Lin Tu; Yu Ma; Xinyue Han; Mingze Zhu (Journal of Cleaner Production, 2023)

Combined effects of NaOH, NaCl, and heat on the characteristics of ovalbumin gel and the exploration of the mechanism of transparent gel formation - Hui Xue; Tianfeng Han; Guowen Zhang; Xiaobo Hu; Ruiling Li; Huilan Liu; Rui Li; Yonggang Tu; Yan Zhao (Food Hydrocolloids, 2023)

Flood risk assessment of metro stations based on the SMAA-2-FFS-H method: a case study of the “7$$·$$20” rainstorm in Zhengzhou, China - Yan Tu; Han Shi; Xiaoyang Zhou; Liyi Liu; Benjamin Lev (Stochastic Environmental Research and Risk Assessment, 2023)

Effective regulation towards electrochemical stability of superionic solid electrolyte via facile dual-halogen strategy - Xuming Luo; Xianneng He; Han Su; Yu Zhong; Xiuli Wang; Jiangping Tu (Chemical Engineering Journal, 2023)

An elevation mask modeling method based on azimuth rounding for monitoring building deformation - Han Junqiang; Tu Rui; Lu Xiaochun; Xiao Xia; Zhang Rui; Fan Lihong; Zhang Pengfei; Wang Siyao (Acta Geodaetica et Geophysica, 2023)

The promotional effects of carbon nanotube on Fe5C2-ZnO catalysts for CO2 hydrogenation to heavy olefins - Haripal Singh Malhi; Zhenzhou Zhang; Yanling Shi; Xinhua Gao; Wenqi Liu; Weifeng Tu; Yi-Fan Han (Fuel, 2023)

Deficiency of RAB39B Activates ER Stress-Induced Pro-apoptotic Pathway and Causes Mitochondrial Dysfunction and Oxidative Stress in Dopaminergic Neurons by Impairing Autophagy and Upregulating α-Synuclein - Ching-Chi Chiu; Yi-Hsin Weng; Tu-Hsueh Yeh; Juu-Chin Lu; Wan-Shia Chen; Allen Han-Ren Li; Ying-Ling Chen; Kuo-Chen Wei; Hung-Li Wang (Molecular Neurobiology, 2023)

AIseed: An automated image analysis software for high-throughput phenotyping and quality non-destructive testing of individual plant seeds - Keling Tu; Weifeng Wu; Ying Cheng; Han Zhang; Yanan Xu; Xuehui Dong; Mang Wang; Qun Sun (Computers and Electronics in Agriculture, 2023)

Anti-inflammatory flavonoid derivatives from the heartwood of Dalbergia odorifera T. Chen - Ni-li Zan; Zi-Han Lu; Xin-Yu Wang; Rong-Ye Wang; Nai-Yun Liang; Hui-Xia Huo; Yun-Fang Zhao; Yue-Lin Song; Peng-Fei Tu; Jiao Zheng; Jun Li (Natural Product Research, 2023)

Bio-inspired citric acid-based bimetallic photocatalyst for nitrogen fixation from air under ambient conditions - Yutong Chen; Qiang Sun; Xuewei Tu; Liangchen Chen; Weihang Han; Luping Zhang; Xiaofei Duan; Min Liu; Hui Zheng (Journal of Cleaner Production, 2023)

Allografts: expanding the surgeon’s armamentarium - Norus Ahmed; Volker Eras; Axel Pruß; Carsten Perka; Jan Brune; Tu-Lan Vu-Han (Cell and Tissue Banking, 2023)
In Germany, bone allografts are widely used and their application in clinics has increased over the years. Successful use of allografts depends on many factors such as the procurement, processing, sterilization and the surgeon’s surgical experience. Tissue banks have provided safe and sterile allografts for decades ranging from hard to soft tissue. Allografts are obtained from various tissues such as bone, tendon, amniotic membrane, meniscus and skin. An advantage of allografts is their wide applicability that has never been limited by indication restrictions thus providing a huge benefit for surgeon’s. The use of the correct allograft in different indications is extremely important. Thereby surgeons have access to various allograft forms such as mineralized, demineralized, freeze-dried, paste, powder, chips strips and putty. The vast options of allografts allow surgeon’s to use allografts in indications they deem fit. Currently, the application of allografts is at the discretion of the expert surgeon. However, regulations are often changed locally or internationally and may impact/limit allograft use to certain indications. Here, we report the different indications where our peracetic acid (PAA) sterilised bone allografts were used as well as general literature on bone allograft use in other indications.

Orbit determination of BeiDou navigation satellite system maneuvered satellites based on instantaneous velocity pulses parameters - Rui Zhang; Rui Tu; Junqiang Han; Pengfei Zhang; Lihong Fan; Siyao Wang; Xiaochun Lu (Advances in Space Research, 2023)

Classifying Temporomandibular Disorder with Artificial Intelligent Architecture Using Magnetic Resonance Imaging - Zih-Kai Kao; Neng-Tai Chiu; Hung-Ta Hondar Wu; Wan-Chen Chang; Ding-Han Wang; Yen-Ying Kung; Pei-Chi Tu; Wen-Liang Lo; Yu-Te Wu (Annals of Biomedical Engineering, 2023)

Preferred prey reduce species realized niche shift and improve range expansion prediction - Lixia Han; Zhixin Zhang; Weishan Tu; Qing Zhang; Yanhua Hong; Shengnan Chen; Zhiqiang Lin; Shimin Gu; Yuanbao Du; Zhengjun Wu; Xuan Liu (Science of The Total Environment, 2023)

In vivo near-infrared fluorescence and SPECT-CT imaging of colorectal Cancer using the bradykinin B2R-specific ligand icatibant - Kaili Qin; Suling Xin; Gang Li; Kuncheng Zhou; Rongbin Pan; Shuying Chen; Tianming Tao; Changsheng Li; Ji Tao; Ray P.S. Han; Yuanbiao Tu (Journal of Photochemistry and Photobiology B: Biology, 2023)

Exploring COVID-19 transmission patterns and key factors during epidemics caused by three major strains in Asia - Han Tu; Xia Wang; Sanyi Tang (Journal of Theoretical Biology, 2023)

Nutritional properties and osteogenic activity of simulated digestion components and peptides from Larimichthys crocea - Zhe Xu; Shiying Han; Hui Chen; Lingyu Han; Xiufang Dong; Maolin Tu; Zhijian Tan; Ming Du; Tingting Li (Food Research International, 2023)

Efficient sunlight promoted nitrogen fixation from air under room temperature and ambient pressure via Ti/Mo composites - Liangchen Chen; Jingxuan Shou; Yutong Chen; Weihang Han; Xuewei Tu; Luping Zhang; Qiang Sun; Jun Cao; Yurong Chang; Hui Zheng (Chemical Engineering Journal, 2023)

A novel ADA-coated UCNPs@NB sensing platform combined with nucleic acid amplification for rapid detection of Escherichia coli - Yaqi Song; Min Chen; Lu Han; Zhongyu Yan; Leiqing Pan; Kang Tu (Analytica Chimica Acta, 2023)

Manganese addition accelerates litter decomposition and alters litter mixing effects in the late stage in subtropical plantations of southern China - Pan-Pan Wu; Ling-Xin Jiang; Yan Zhang; Qi-Han Tu; Rong Mao (Plant and Soil, 2022)

Simulation and risk assessment of typical antibiotics in the multi-media environment of the Yangtze River Estuary under tidal effect - Chaomeng Dai; Yueming Han; Yan Li; Yanping Duan; Shuguang Liu; Yalei Zhang; Yaojen Tu (Environmental Science and Pollution Research, 2022)

Heritability estimates for gonadal development traits and their genetic correlations with growth and heat tolerance traits in the Fujian Oyster Crassostrea angulata - Ziqiang Han; Xiang Guo; Zuoliang Lu; Yiheng Song; Ruimin Chen; Xiaojie Han; Shiqi Yu; Kang Tu; Liangjie Liu; Huayong Que (Frontiers in Marine Science, 2022)
Improving the progress of breeding is the main purpose of breeders, and shorting the reproductive cycle is one of the ways to improve the breeding progress. Although the reproductive cycle of Crassostrea angulata can be shortened from one year to half a year by selecting precocious individuals, little is known about whether this selection will accelerate their gonadal development or disturb their selection for productive traits. Here, the heritability of gonadal development traits (gametogenic stage and egg diameter) and their genetic correlations with both growth traits (shell height at 4 and 12 months and total body weight at 12 months) and heat tolerance trait were estimated. The heritability for gametogenic stage was low (0.18 ± 0.09), while the egg diameter showed a high heritability (0.78 ± 0.30). These results suggest that selection for precocious individuals has little effect on the rate of gonadal development in the C. angulata , despite the effect may be greater in females than in males. The genetic correlations between gonadal development traits and both growth (-0.02–0.30) and heat tolerance traits (-0.08–0.34) were low and non-significant. These results suggest that selection for precocious individuals has negligible effects on their productive traits. Therefore, it is feasible to double the breeding efficiency of C. angulata by halving their reproductive cycle.

Putative role of corazonin in the ovarian development of the swimming crab Portunus trituberculatus - Shisheng Tu; Fuqiang Ge; Yaoyao Han; Mengen Wang; Xi Xie; Dongfa Zhu (Frontiers in Marine Science, 2022)
Corazonin (Crz) is a neuropeptide that widely distributed in insects and crustaceans. The Crz is proposed to have pleiotropic functions in insects, but its physiological roles in crustaceans are poorly understood. In the present study, Crz and its putative receptor ( CrzR ) were identified from the swimming crab, Portunus trituberculatus , and their interaction was validated using the Dual-Luciferase reporter assay system. Tissue distribution analysis showed the PtCrz was mainly derived from center nerve system, while its receptor was highly expressed in Y-organ, the main site for ecdysteroids synthesis. Exposure of YO to synthetic Crz and CrzR dsRNA respectively led to the transcriptional changes of two ecdysteroidogenesis genes, further indicating a putative role of Crz signaling on ecdysteroids synthesis. During the ovarian development, the mRNA levels of PtCrz and PtCrzR increased significantly in vitellogenic stages, suggesting a potential role of Crz signaling in vitellogenesis. The hypothesis was further strengthened by in vitro experiments that the expression of vitellogenin ( Vg ), Vg receptor ( VgR ), cyclinB , and Cdc2 in ovary explants could be induced by synthetic Crz, whereas reduced by CrzR dsRNA. In addition, since 20-hydroxyecdysone also showed a stimulating effect on Vg expression, an indirect regulation of Crz signaling on ovarian development via ecdysteroids might also exist.

Identification of novel biofilm genes in avian pathogenic Escherichia coli by Tn5 transposon mutant library - Jiangang Hu; Yi Gu; Huiqi Lu; Muhammad Akmal Raheem; Fangheng Yu; Xiangpeng Niu; Jiakun Zuo; Huifang Yin; Cuiqin Huang; Xiangjun Song; Jian Tu; Wen Zhou; et al. (World Journal of Microbiology and Biotechnology, 2022)

Characterization and Complete Genomic Analysis of Vibrio Parahaemolyticus-Infecting Phage KIT05 - Vo Thi Tu Anh; Nguyen Huan Pham-Khanh; Nguyen Song Han; Hirofumi Sunahara; Kaeko Kamei (Current Microbiology, 2022)

Impact of CT-Based and MRI-Based Attenuation Correction Methods on 18 F-FDG PET Quantification Using PET Phantoms - Cheng-Han Wu; Chun-Yuan Tu; Li-Chen Shen; Yueh-Hsun Lu; Bang-Hung Yang (Journal of Medical and Biological Engineering, 2022)

Correction to: 2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

2021 Taxonomic update of phylum Negarnaviricota (Riboviria: Orthornavirae), including the large orders Bunyavirales and Mononegavirales - Jens H. Kuhn; Scott Adkins; Bernard R. Agwanda; Rim Al Kubrusli; Sergey V. Alkhovsky; Gaya K. Amarasinghe; Tatjana Avšič-Županc; María A. Ayllón; Justin Bahl; Anne Balkema-Buschmann; Matthew J. Ballinger; Christopher F. Basler; et al. (Archives of Virology, 2021)

The protective effect of hydrogen-rich water on rats with type 2 diabetes mellitus - Mengna Zheng; Han Yu; Yong Xue; Tong Yang; Qiufen Tu; Kaiqing Xiong; Daihua Deng; Lei Lu; Nan Huang (Molecular and Cellular Biochemistry, 2021)

Gene knockout revealed the role of gene feoA in cell growth and division of Lactobacillus delbrueckii subsp. bulgaricus - Xue Han; Yuanqiang Tu; Huiying Wu; Lijuan Zhang; Sainan Zhao (Archives of Microbiology, 2021)

Using the Metabolome to Understand the Mechanisms Linking Chronic Arsenic Exposure to Microglia Activation, and Learning and Memory Impairment - Rui-Yuan Zhang; Jie-Bai Tu; Rui-Tu Ran; Wen-Xuan Zhang; Qiang Tan; Ping Tang; Tao Kuang; Shu-Qun Cheng; Cheng-Zhi Chen; Xue-Jun Jiang; Chang Chen; Ting-Li Han; et al. (Neurotoxicity Research, 2021)

Precise frequency transfer model suitable for short baseline link based on GPS single-differenced observations with ambiguity resolution - Rui Tu; Pengfei Zhang; Rui Zhang; Lihong Fan; Junqiang Han; Ju Hong; Jinhai Liu; Xiaochun Lu (Acta Geodaetica et Geophysica, 2021)

Accelerated remediation of organochlorine pesticide-contaminated soils with phyto-Fenton approach: a field study - Trinh Dinh Tran; Nhung Thi Dao; Rei Sasaki; Minh Binh Tu; Giang Huong Minh Dang; Han Gia Nguyen; Hieu Minh Dang; Cong Huu Vo; Yoshihiko Inigaki; Noi Van Nguyen; Yutaka Sakakibara (Environmental Geochemistry and Health, 2020)

Model test and numerical simulation on the dynamic stability of the bedding rock slope under frequent microseisms - Zhiyun Deng; Xinrong Liu; Yongquan Liu; Shulin Liu; Yafeng Han; Jinhui Liu; Yiliang Tu (Earthquake Engineering and Engineering Vibration, 2020)

Estimating purple-soil moisture content using Vis-NIR spectroscopy - Yu Gou; Jie Wei; Jin-lin Li; Chen Han; Qing-yan Tu; Chun-hong Liu (Journal of Mountain Science, 2020)

A model to obtain timing solution with un-differenced observations suitable for single-station/multi-station, a case study of BDS data - Pengfei Zhang; Rui Tu; Rui Zhang; Junqiang Han; Lihong Fan (Acta Geodaetica et Geophysica, 2020)

Microalgae harvesting by magnetic flocculation for biodiesel production: current status and potential - Song-Fang Han; Wenbiao Jin; Renjie Tu; Shu-Hong Gao; Xu Zhou (World Journal of Microbiology and Biotechnology, 2020)

Cumulative damage evolution and failure modes of the bedding rock slope under frequent microseisms - Zhiyun Deng; Xinrong Liu; Yongquan Liu; Shulin Liu; Yafeng Han; Yiliang Tu; Jun Gu (Arabian Journal of Geosciences, 2020)

Performance of Galileo precise time and frequency transfer models using quad-frequency carrier phase observations - Pengfei Zhang; Rui Tu; Yuping Gao; Rui Zhang; Junqiang Han (GPS Solutions, 2020)

Enhanced removal of phosphate and ammonium by MgO-biochar composites with NH3·H2O hydrolysis pretreatment - Ran Xiao; Han Zhang; Zhineng Tu; Ronghua Li; Songling Li; Zhongyang Xu; Zengqiang Zhang (Environmental Science and Pollution Research, 2020)

Model test on the bearing behaviors of the tunnel-type anchorage in soft rock with underlying weak interlayers - Yafeng Han; Xinrong Liu; Dongliang Li; Yiliang Tu; Zhiyun Deng; Dongshuang Liu; Xiangchao Wu (Bulletin of Engineering Geology and the Environment, 2020)

Geochemical behaviors of antimony in mining-affected water environment (Southwest China) - Ling Li; Han Tu; Shui Zhang; Linna Wu; Min Wu; Yang Tang; Pan Wu (Environmental Geochemistry and Health, 2019)

Municipal Wastewater Enriched with Trace Metals for Enhanced Lipid Production of the Biodiesel-Promising Microalga Scenedesmus obliquus - Song-Fang Han; Wenbiao Jin; Abd El-Fatah Abomohra; Renjie Tu; Xu Zhou; Zhongqi He; Chuan Chen; Guo-jun Xie (BioEnergy Research, 2019)

Cloning, molecular characterization, and tissue differential expression of connective tissue growth factor (ctgf) of grass carp - Wen-Qian Pan; Jun-Peng Wang; Zhi-Han Tu; Tian Gan; Jing Hu; Jing Wei; Xiang-Jun Leng; Xiao-Qin Li (Fish Physiology and Biochemistry, 2019)

Seismic imaging of the Formosa Ridge cold seep site offshore of southwestern Taiwan - Ho-Han Hsu; Char-Shine Liu; Sumito Morita; Shu-Lin Tu; Saulwood Lin; Hideaki Machiyama; Wataru Azuma; Chia-Yen Ku; Song-Chuen Chen (Marine Geophysical Research, 2018)

Knockout of ush2a gene in zebrafish causes hearing impairment and late onset rod-cone dystrophy - Shanshan Han; Xiliang Liu; Shanglun Xie; Meng Gao; Fei Liu; Shanshan Yu; Peng Sun; Changquan Wang; Stephen Archacki; Zhaojing Lu; Xuebin Hu; Yayun Qin; et al. (Human Genetics, 2018)

Postnatal Subacute Benzo(a)Pyrene Exposure Caused Neurobehavioral Impairment and Metabolomic Changes of Cerebellum in the Early Adulthood Period of Sprague-Dawley Rats - Chunlin Li; Jing Wang; Qiuping Su; Kai Yang; Chengzhi Chen; XueJun Jiang; Tingli Han; Shuqun Cheng; Tingting Mo; Ruiyuan Zhang; Bin Peng; Yuming Guo; et al. (Neurotoxicity Research, 2018)

Subcritical n-hexane/isopropanol extraction of lipid from wet microalgal pastes of Scenedesmus obliquus - Xiaoyu Bian; Wenbiao Jin; Qiong Gu; Xu Zhou; Yuhe Xi; Renjie Tu; Song-Fang Han; Guo-Jun Xie; Shu-Hong Gao; Qilin Wang (World Journal of Microbiology and Biotechnology, 2018)

Seasonal variability of oxygen and hydrogen isotopes in a wetland system of the Yunnan-Guizhou Plateau, southwest China: a quantitative assessment of groundwater inflow fluxes - Xingxing Cao; Pan Wu; Shaoqi Zhou; Zhiwei Han; Han Tu; Shui Zhang (Hydrogeology Journal, 2018)

Two new cadinane-type sesquiterpenes from cultures of the basidiomycete Trichaptum pargamenum - Bin Tang; Xi Du; Han-An Long; Jun Du; Jian-Min Guo; Xin Hu; Hua Tu; Li Yang; Hong-Jin Liu (Natural Product Research, 2017)

Sources, Spatial Distribution, and Seasonal Variation of Major Ions in the Caohai Wetland Catchment, Southwest China - Xingxing Cao; Pan Wu; Zhiwei Han; Shui Zhang; Han Tu (Wetlands, 2016)

Improving of lipid productivity of the biodiesel promising green microalga Chlorella pyrenoidosa via low-energy ion implantation - Renjie Tu; Wenbiao Jin; Mu Wang; Songfang Han; Abd El-Fatah Abomohra; Wei-Min Wu (Journal of Applied Phycology, 2016)

Humic acids enhance the microbially mediated release of sedimentary ferrous iron - Chun-Han Chang; Chia-Cheng Wei; Li-Hung Lin; Tzu-Hsuan Tu; Vivian Hsiu-Chuan Liao (Environmental Science and Pollution Research, 2016)

The effective mode of growth and differentiation factor-5 in promoting the chondrogenic differentiation of adipose-derived stromal cells - Changxu Han; Yizhong Ren; Yanbo Jia; Lingyue Kong; Tu Eerdun; Lishuan Wu (Cell and Tissue Banking, 2016)

Zircon U–Pb dating constraints on the crustal melting event around 8 Ma in the eastern Himalayan syntaxis - Ji-Yao Tu; Jian-Qing Ji; Jun-Feng Gong; Quan-Ren Yan; Bao-Fu Han (International Geology Review, 2016)

Validation of cross-contamination control in biological safety cabinet for biotech/pharmaceutical manufacturing process - Shih-Cheng Hu; Angus Shiue; Jin-Xin Tu; Han-Yang Liu; Rong-Ben Chiu (Environmental Science and Pollution Research, 2015)

Retraction Note to: Identification of genes associated with the differentiation potential of adipose-derived stem cells to osteocytes or myocytes - Yizhong Ren; Changxu Han; Jingjuan Wang; Yanbo Jia; Lingyue Kong; Tu Eerdun; Lishuan Wu; Dianming Jiang (Molecular and Cellular Biochemistry, 2015)

Up-regulation of SPOCK1 induces epithelial–mesenchymal transition and promotes migration and invasion in esophageal squamous cell carcinoma - Xiaopeng Song; Ping Han; Jingmei Liu; Yunwu Wang; Dongxiao Li; Jiayi He; Jin Gong; Mengke Li; Wei Tu; Wei Yan; Mei Liu; Huanjun Huang; et al. (Journal of Molecular Histology, 2015)

Growth, V uptake, and antioxidant enzymes responses of chickpea (Cicer arietinum L.) genotypes under vanadium stress - Muhammad Imtiaz; Shuxin Tu; Zhijian Xie; Dan Han; Muhammad Ashraf; Muhammad Shahid Rizwan (Plant and Soil, 2015)

RETRACTED ARTICLE: Identification of genes associated with the differentiation potential of adipose-derived stem cells to osteocytes or myocytes - Yizhong Ren; Changxu Han; Jingjuan Wang; Yanbo Jia; Lingyue Kong; Tu Eerdun; Lishuan Wu; Dianming Jiang (Molecular and Cellular Biochemistry, 2015)

Design, synthesis, and biological study of 6,7-dihydro-5H-pyrano[2,3-d]pyrimidine derivatives as novel hedgehog signaling pathway inhibitors - Minhang Xin; Liandi Zhang; Han Shen; Jun Wen; Chongxing Tu; Zhaoyu Liu; Lingfei Cheng; Xinge Zhao (Medicinal Chemistry Research, 2014)

Construction of Escherichia coli strains producing l-serine from glucose - Yu Li; Gu-Kui Chen; Xin-Wei Tong; Hui-Tu Zhang; Xiao-Guang Liu; Yi-Han Liu; Fu-Ping Lu (Biotechnology Letters, 2012)

Early subduction–exhumation and late channel flow of the Greater Himalayan Sequence: implications from the Yadong section in the eastern Himalaya - Junfeng Gong; Jianqing Ji; Baofu Han; Jianjun Chen; Dongxia Sun; Baolong Li; Jing Zhou; Jiyao Tu; Dalai Zhong (International Geology Review, 2012)

Curcumin protects mice against concanavalin A-induced hepatitis by inhibiting intrahepatic intercellular adhesion molecule-1 (ICAM-1) and CXCL10 expression - Chuan-tao Tu; Bing Han; Hong-chun Liu; Shun-cai Zhang (Molecular and Cellular Biochemistry, 2011)

Aerobic swimming performance of juvenile Schizothorax chongi (Pisces, Cyprinidae) in the Yalong River, southwestern China - Zhiying Tu; Xi Yuan; Jingcheng Han; Xiaotao Shi; Yingping Huang; David Johnson (Hydrobiologia, 2011)

Shiga toxin type 2 (Stx2), a potential agent of bioterrorism, has a short distribution and a long elimination half-life, and induces kidney and thymus lesions in rats - Yue-Nan Liu; Sheng-han Wang; Tao Li; Qin Wang; Wei Tu; Kun Cai; Xiao-Jun Hou; Ren-Mao Tian; Xiang Gao; Hao Liu; Le Xiao; Jing Shi; et al. (Archives of Toxicology, 2011)

Fungal Communities in Decaying Sapwood and Heartwood of a Conifer Keteleeria evelyniana - Han-Bo Zhang; Ming-Xia Yang; Ran Tu; Lei Gao; Zhi-Wei Zhao (Current Microbiology, 2008)

Effect of Cadmium in Feed on Organs and Meat Colour of Growing Pigs - Y.-J. Tu; X.-Y. Han; Z.-R. Xu; Y.-Z. Wang; W.-F. Li (Veterinary Research Communications, 2007)

Nonylphenol Induced Apoptosis in Rat Testis Through the Fas/FasL Pathway - X. Han; Z. Tu; X. Wang; S. Shen; Y. Hou (Bulletin of Environmental Contamination and Toxicology, 2004)